2020
DOI: 10.3892/ol.2020.11307
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema in survivors of breast cancer (Review)

Abstract: The tremendous improvement of survival in patients with breast cancer can be attributed to several treatment strategies, but these strategies also lead to the occurrence of breast cancer-related lymphedema (BCRL). BRCL is regularly associated with factors such as axillary lymph node dissection and local lymph node radiotherapy and manifests as an increase of >10% in the volume of affected limbs. Being overweight or having obesity (body mass index ≥25 kg/m 2 ), an excessive number of positive lymph nodes (>8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 133 publications
(133 reference statements)
2
42
0
4
Order By: Relevance
“…In the field of lymphoedema treatment in female breast cancer survivors, there are several research works in which the benefits of exercise treatment in reducing lymphoedema have been collected [36][37][38][39]. In the studies of DiSipo et al [9] and Baumann et al [25] subjective improvements in the quality of life of the patients, anxiety (as occurs in other pathologies that alter the quality of life [40,41]), the decrease in lymphoedema (evaluated with volumetry) and, equally important, the non-appearance of adverse effects in the study population, are revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of lymphoedema treatment in female breast cancer survivors, there are several research works in which the benefits of exercise treatment in reducing lymphoedema have been collected [36][37][38][39]. In the studies of DiSipo et al [9] and Baumann et al [25] subjective improvements in the quality of life of the patients, anxiety (as occurs in other pathologies that alter the quality of life [40,41]), the decrease in lymphoedema (evaluated with volumetry) and, equally important, the non-appearance of adverse effects in the study population, are revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Nine RCTs published between 2006 and 2019 were included, with a total of 1147 patients distributed in groups of 21-104 women. The selected articles evaluated the effect of therapeutic strength [2,7,8,[31][32][33][34] or aerobic [2,30,34,36] exercise on the swelling of the affected upper limb in women who had been surgically intervened for breast cancer; three of these articles also included stretching exercises in their intervention programmes [31,33,34]. Strength training was understood as exercises with weights, dumbbells, variable-resistance machines, and thera-bands, whereas aerobic training was understood as activities such as walking; on the other hand, exercises with hand crank ergometers were considered as combined strength and aerobic training.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The initial signs of BCRL are swelling and discomfort in the forearm area that disappears when lifting the affected area or by external compression [12,21]. Moderate to severe stages of BCRL consist of changes of the skin structure or appearance of peau d'orange (skin texture that resembles orange peel) that becomes bigger and is no longer relieved by lifting or external pressure [22]. The continuous expansion of fibrotic tissue and fat deposition affects the thickness of the skin and subcutaneous tissue, leading to the hardening of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…However, lymphedema still occurs in 7% of patients undergoing SLNB (2). Lymphedema severely affects the quality of life of BC patients due to the lifestyle and occupational alternations, change in the functional status, as well as changes in the psychosocial and economic aspects (3). The clinical signs vary with the duration and severity of lymphedema, from vague…”
Section: Introductionmentioning
confidence: 99%